VUV PROPERTIES OF Eu3+- DOPED YBO3 PHOSPHOR PREPARED VIA ALDO-KETO AND SOLID-STATE PROCESS - Wankhade, R N; Bajaj, N S; Korpe, G V; Bhatkar, V B; Omanwar, S K (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The Eu3+ doped YBO3 was prepared by the novel aldo-keto method. The structure and VUV luminescence properties of the title compound were studied and compared to the corresponding properties of the materials prepared by a conventional solid state reaction. The use of novel aldo-keto method in preparation lowered the reaction threshold temperature by c.a. 300oC. The YBO3 phosphor from the aldo-keto method look like evenly sized spherical structures, whereas those from the solid-state process look like some agglomerates of little spheres. The Eu3+-doped YBO3 phosphors prepared by both methods showed the red emission with peak around 592, 611 and 627 nm at excitations wavelengths 147 and172 nm, which corresponds to the transitions from the excited 5D0 level to the 7FJ (J = 1, 2, 3, 4) levels of Eu3+ activators. However, the emission intensity of the Eu3+ doped YBO3 from the aldo-keto system is about 2 times as much as that from the sold-state process.